Physician-Assisted Suicide and Euthanasia: Before, During, and After the Holocaust - Rubenfeld, Sheldon; Sulmasy, Daniel P. (Lexington Books, 2020)
Unlike Nazi medical experiments, euthanasia during the Third Reich is barely studied or taught. Often, even asking whether euthanasia during the Third Reich is relevant to contemporary debates about physician-assisted suicide (PAS) and euthanasia is dismissed as inflammatory. Physician-Assisted Suicide and Euthanasia: Before, During, and After the Holocaust explores the history of euthanasia before and during the Third Reich in depth and demonstrate how Nazi physicians incorporated mainstream Western philosophy, eugenics, population medicine, prevention, and other medical ideas into their ideology. This book reveals that euthanasia was neither forced upon physicians nor wantonly practiced by a few fanatics, but widely embraced by Western medicine before being sanctioned by the Nazis. Contributors then reflect on the significance of this history for contemporary debates about PAS and euthanasia. While they take different views regarding these practices, almost all agree that there are continuities between the beliefs that the Nazis used to justify euthanasia and the ideology that undergirds present-day PAS and euthanasia. This conclusion leads our scholars to argue that the history of Nazi medicine should make society wary about legalizing PAS or euthanasia and urge caution where it has been legalized.